An evaluation of the effectiveness of counter-violent extremism measures in the Malaysian Armed Forces / Nizlan Mohamed - Nizlan , Mohamed (2020)
This research was conducted to evaluate the effectiveness of counter-violent extremism (CVE) measures in the Malaysian Armed Forces (MAF). The issue of violent extremism and terrorism has implications on the MAF in terms of the involvement of some of its personnel in such activities. The MAF has introduced CVE measures to curb this phenomenon from escalating. This research was carried out to examine measures undertaken involving two groups of participants from the MAF. The first group comprised military personnel who had undergone PERISAI SATRIA, a de-radicalization program while the second group was military personnel exposed to Task Force PERISAI WIRA, a roadshow program. Both are CVE measures under the supervision of the Defence Intelligence Staff Division (DISD) of the MAF. This study uses the qualitative method. Case study research is adopted whereby data are collected from individual interviews comprising military personnel from the Malaysian Army, Royal Malaysian Navy and Royal Malaysian Air Force services. An interview protocol is designed as a guideline for the researcher to conduct this study and semi-structured questions were posed to all participants. All data are analysed using the Nvivo 12 tools method, a Computer Assisted Qualitative Data Analysis Software (CAQDAS) program and manual interpretation to have a systematic and comprehensive data output. The findings of this dissertation indicate that suspected military personnel are inclined to be involved in violent extremism domains based on psychological manifestation, religiosity fundamentals and other management issues. Other issues that influence military personnel involved in violent extremism were also identified. This research proposessuggestions and recommendations to improve the current counterviolent extremism efforts in the MAF. The study hopes to make a significant contribution to the organization in terms of improving the counter-violent extremism mechanism for preventing or mitigating the terrorism phenomenon. It is also hoped that this study will provide valuable insights for current and future global efforts against violent extremism.